The effect of production parameters on the foaming behavior of spherical-shaped aluminum foam - Uzun, Arif; Turker, Mehmet (FapUNIFESP (SciELO), 2014)
The effect of production parameters on the foaming behavior of spherical-shaped aluminum foam was studied. Elemental powders of Alumix 231 and 1% TiH2 were mixed, compacted at 600 MPa pressure by using a uniaxial action press to produce blanks with 50×30×10 mm in dimensions. These blanks were pre-heated at 550 °C in a furnace for 180 min and then deformed by 10, 30, 50 and 70% by using an eccentric press. They were cut into square shape and foamed at temperatures between 650 °C and 710 °C. It was experimentally found that, the volume expansion rate of foam increases but the maximum foaming duration decreases with increasing the deformation rate and foaming temperature. In these studies 70% deformation and 3.5 minutes foaming duration were found to be the best for the production of spherical foams. This was determined by obtaining the maximum expansion, lower density and homogeneously distributed pores with spherical foams. It was also found that 10% deformation rate was not enough for foaming.
Keywords: powder metallurgy; porosity; Al foam; TA401-492; APM foam; Materials of engineering and construction. Mechanics of materials; 13. Climate action; 7. Clean energy